Dampak Produk, Harga dan Lokasi Terhadap Keputusan Pembelian Konsumen di Pasar Tradisional - Dewinta Sari; Rikkie Dekas; Teuku Muhammad Haqiqi (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine the impact of production, price and location on consumer purchasing decisions at the Sukajadi traditional market, Banyuasin Regency. Data collection using a questionnaire (Questionnaire). The results of the research show that the Validation Test of product variables, price variables, location variables and purchasing decision variables has a critical value for the sample at a significant level of 5%. indicates that all items of product variable questions, price variables, location variables and purchasing decision variables are valid. Thus the measuring instrument used in this study is suitable for measuring product variables, price variables, location variables and purchasing decision variables. Reliability test for product variable, price variable, location variable and purchase decision variable shows that all variables are reliable. Conclusion, Product variable Validation Test, Price variable, Location Variable and Purchasing Decision variable at the critical value for the sample at a significant level of 5% is 0.361. Keywords: Price, Purchase Decision, Location, Product